2011
DOI: 10.1111/j.1365-2923.2011.03986.x
|View full text |Cite
|
Sign up to set email alerts
|

Student views of research training programmes in medical schools

Abstract: CONTEXT Research activity is not a mandatory component of medical education in many developing countries, including Brazil, although such experiences can have a positive impact on the quality of medical education. The interest and involvement of medical students in research and the barriers they face in accessing research training in developing countries have not been adequately addressed.OBJECTIVES We sought to assess the availability of scientific training programmes in Brazilian medical schools, the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 24 publications
2
83
0
20
Order By: Relevance
“…Our result findings depict that still a high percentage of students is more favourable towards old fashioned lecture centred method [7]. There are various types of publications during the same period describing the increased interest in medical research on teaching [8]. Giving lecture notes is a debatable question.…”
Section: Discussionmentioning
confidence: 91%
“…Our result findings depict that still a high percentage of students is more favourable towards old fashioned lecture centred method [7]. There are various types of publications during the same period describing the increased interest in medical research on teaching [8]. Giving lecture notes is a debatable question.…”
Section: Discussionmentioning
confidence: 91%
“…However, we required more efforts in developing countries than developed countries, where EBES has been started earlier in many other ways than developing countries. [14][15][16] Our study showed the 90.9% students believe that research in medical fi eld is important, while approximately 40% students believed that medical students should not know about research methodology, may be due to variety of factors include lack of knowledge, excessive study burden and many other indifferent attitude, need to be identifi ed and approached. 17,18 The study observed various barriers for research, they are time and expenditure for study.…”
Section: Discussionmentioning
confidence: 99%
“…(Burgoyne et al, 2010). 무엇보다 학생 연구활동의 잠재적 장벽에 대한 연구가 부족한 실정이다 (Park et al, 2010;Sabzwari et al, 2009 (Amin et al, 2012;De Oliveira et al, 2011;Memarpour et al, 2015;Nazha et al, 2015;Van Schravendijk et al, 2013 Values are presented as number (%). Values are presented as number of responses (%).…”
Section: 또한 연구에 대한 학생들의 태도는 연구 관련 이전 교육과 스킬 동기 부여된 교수 학교의 동기 부여적 보상unclassified